HUBUNGAN PENGETAHUAN, SIKAP DAN PERILAKU IBU BALITA TERHADAP STUNTING DI KECAMATAN KUTA BARO - Cut Ana Martafari; Rizka Utari Maulina (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Stunting is a nutritional status problem that mostly occurs among toddlers. Nutritional status is one of indicators of health that is commonly related to infants and toddlers due to the rapid growth and development of their body organs, that requires adequate and balanced nutritional intake. For this reason, knowledge, attitudes and behavior of toddlers are very crucial in prevention of stunting. The purpose of this study was to determine the correlation between maternal knowledge (X1), attitudes (X2) and behavior on toddler (X3) against stunting (Y). This research employed a quantitative method. The sample was determined by using the Slovin formula with a total of 91 people. The data was collected through questionnaire, then was analyzed using a simple linear regression formula. From the results of data processing, the r value for X1 is 0.063. This value indicates a very low relationship to Y. The r value for X2 is 0.118. This value indicates a very low relationship to Y. The r value for X3 is 0.295. Likewise, this value shows a low relationship to Y. The hypothesis proof results the tcount for X1 is 7,872, X2 is 3,575 and X3 is 2,136 with a t-table value is 1,662, the value is smaller than t, thus there is a positive and significant relationship between maternal knowledge, attitudes and behavior on toddler against stunting. Simultaneously, the r value is 0.309, this value indicates a low relationship between X1, X2 and X3 to Y. Based on the results of the hypothesis proof, it is obtained that the Fcount is 3.070 with a significant level Î± = 0.05 or 5%, which resulted Ftable of 2.71. That Fcount Ftable, so the basic hypothesis is accepted and the alternative hypothesis is rejected. Therefore, it can be concluded that there is a positive and significant relationship between maternal knowledge (X1), attitudes (X2) and behavior on toddlers(X3) against stunting (Y) in the working area of the Kuta Baro Public Health Center in Aceh Besar.Keywords: Knowledge, Attitudes, Behavior, Stunting